Best Approximation of Data Distributed in a Band. (13th September 2011) - Cuenya, H.; Levis, F.; Rodriguez, C.
Abstract : We study the problem to approximate a data set which are affected in a such way that they present us as a band in the plane. We introduce a deviation measure, and we research the asymptotic behavior of the best approximants when the band shrink in some sense.